A public health approach to fall and injury prevention among seniors in Canada. (1st March 2011) - Scott, V; Herman, M; Gallagher, E; Sum, A
Abstract : Introduction: The need to prevent falls and related injuries among seniors is a significant public health issue in Canada, and all nations where an aging demographic puts higher numbers at risk. To address this costly and complex problem, a sustained collaboration has occurred over the past 20 years among falls prevention leaders within government, the health system, academia and local communities. Methods: This review summarizes key elements of a coordinated, public health approach to the prevention of falls and related injuries among those aged 65 years, with an epidemiological analysis of fall-related hospital and mortality data for persons aged 65 years and older. Review methods included a synthesis of historical records, a scan of existing programs and findings from in-depth interviews with key informants. Results: Outcomes of this sustained approach include a significant reduction in fall-related hospitalization and death rates in some Canadian provinces, which is paralleled by a growth in evidence-based falls prevention programs and services for those at risk. Conclusion: This presentation concludes with a summary of the key developments in the evolution of fall and related injury prevention activities over the past two decades. In particular, how the sustained, collaborative efforts have resulted in Canada emerging as an example of success in the formation of comprehensive networks for the integration of evidence-based falls prevention into health service delivery for seniors.